2022
DOI: 10.1002/jccs.202200421
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin functionalization of gold nanostars for sensitive detection of foodborne pathogens through surface‐enhanced Raman scattering

Abstract: In this paper, we report a sensitive surface-enhanced Raman scattering (SERS) biosensor for the detection of food-borne pathogens on the basis of recognition of bacterial cells through the specific targeting agent vancomycin. Vancomycin-functionalized gold nanostars (GNSs-4-MBA-van) were synthesized as SERS tags for specific and sensitive quantification of food pathogens.The Raman reporter molecule 4-mercaptobenzoic acid (4-MBA) was also a linker molecule to attach vancomycin to gold nanostars. The proposed va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…It can be found that the enhanced Raman signals detected by Au@AgNPs and AuNPs were both relatively weak. The Raman enhancement factor (EF) can be determined using the following equation [64]: EF=ISERS/IRAMAN×CRAMAN/CSERS where I SERS denotes the intensity of analytes obtained by SERS, the conventional Raman intensity of the analytes is denoted by I RAMAN ; C RAMAN is the concentration of Raman molecules in the absence of SERS active substrates, and C SERS is the concentration of analytes obtained by SERS substrates, respectively. The EF calculations indicated an increase in the enhancement factors of Tbz from 6.2 × 10 2 with AuNPs, 4.5 × 10 4 with Au@AgNPs, and 2.0 × 10 5 with Au@Ag@CysNPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found that the enhanced Raman signals detected by Au@AgNPs and AuNPs were both relatively weak. The Raman enhancement factor (EF) can be determined using the following equation [64]: EF=ISERS/IRAMAN×CRAMAN/CSERS where I SERS denotes the intensity of analytes obtained by SERS, the conventional Raman intensity of the analytes is denoted by I RAMAN ; C RAMAN is the concentration of Raman molecules in the absence of SERS active substrates, and C SERS is the concentration of analytes obtained by SERS substrates, respectively. The EF calculations indicated an increase in the enhancement factors of Tbz from 6.2 × 10 2 with AuNPs, 4.5 × 10 4 with Au@AgNPs, and 2.0 × 10 5 with Au@Ag@CysNPs.…”
Section: Resultsmentioning
confidence: 99%
“…It can be found that the enhanced Raman signals detected by Au@AgNPs and AuNPs were both relatively weak. The Raman enhancement factor (EF) can be determined using the following equation [64]:…”
Section: Raman Enhancement Mechanism Of Au@ag@cysnpsmentioning
confidence: 99%
“…Similarly, bio-chromic conjugated polymers (BCPs) are bio-mimetic biosensors made of conjugated polymers with optical properties suitable for incorporating biologically active cell membrane compounds (Velusamy et al, 2010). Polydiacetylenic cell membrane-mimicking materials aid in the detection of pathogens, toxins and viruses through visible color change and colorimetric detection (Velusamy et al, 2010;Li et al, 2022;Dou et al, 2020). However, it has been observed that BCPs are convenient to use and microfabricate, while MIPs face challenges like imprinted polymer insolubility and the difficult procedure of template removal (Velusamy et al, 2010).…”
Section: Nfs 541mentioning
confidence: 99%
“…Since simple and sensitive detection of this pathogen has always remained a challenge, the development of this sensor will prove beneficial in food safety applications (Duan et al , 2016). In another study, Dayalan et al (2022) also developed the SERS biosensor for the detection of food-borne pathogens. In this study, they recognized the bacterial cells through the specific targeting agent vancomycin having a detection limit of 8.2 and 5.7 CFU/mL for Escherichia coli and Staphylococcus aureus , respectively.…”
Section: Classification Of Biosensormentioning
confidence: 99%
“…Infectious and chemical contaminants threaten aquatic life and human health worldwide [1][2][3]. Water quality in the environment is deteriorating rapidly due to numerous factors, including the introduction of pathogenic microorganisms and the release of toxic waste containing dyes [4].…”
Section: Introductionmentioning
confidence: 99%